Effect of Self-Directed Videos and Simulations on Nurse Skills in Advanced Cardiac Life Support: Comparison Study - Jatim Sugiyanto; Karyono Mintaroem; Titin Andri Wihastuti (Research Journal of Life Science, 2020)
Cardiac arrest is one of the highest causes of death in the world. This condition requires the handling of cardiac arrest based on the chain of survival concept. The chain of survival concept is carried out by nurses who have sufficient skills to handle cardiac arrest. Skills can be obtained either through education and training based on simulation or using technology such as self-directed videos. The purpose of this study was to identify the differences in self-direct video and simulations of nurse skills in advanced cardiac life support. This study used Quasi-Experimental Design by pretest-posttest with a control group approach. The 42 respondents were divided into two groups. Skills are measured before and after learning with each method. Data were analyzed using Wilcoxon and Mann-whitney tests. The results showed changes in skills before and after learning in the two methods, with each p-value = 0.000. There were no differences in skills changes before and after learning in both groups with a p-value = 0.437. Learning using self-directed videos and simulations can improve nurse skills in carrying out advanced cardiac life support.